ICT Based Weather Information and Agro Advisory Services - CGIAR Research Program on Climate Change, Agriculture and Food Security; BAIF Development Research Foundation (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
11,250 farmers from 75 villages in the three project districts are being assisted to access weather forecast information and agro advisory, to better adapt to the impending weather events. Weather information and agricultural advisory (extension) services have long been recognized as an important factor in promoting agricultural development. As part of the USAID project, a mobile phone-based information dissemination system has been established in three districts i.e. Mathura (Uttar Pradesh), Nalanda (Bihar) and Betul (Madhya Pradesh) in India. A total of 3,750 farmers from 25 villages in each district are being assisted with weather forecast information and agro advisory services.